1994
DOI: 10.7124/bc.0003bb
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic variability in natural Drosophila populations

Abstract: The paper describes the origin and development of population genetics, its main disco veries achieved in experiments with Drosophila before 1948 breakage and summarized the results of two series of long-term studies on genetic variability in Drosophila car ried out by the authors. The conceptual contribution of two main centers or school leaded by N. Koltzov and S. Chetverikov in Moscow and Yu. Filipchenko in St.-Pelersburg is considered. The ideas and methodology of these schools were introduced into American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The 1(2)gl gene is the most distal locus on the left arm of chromosome 2. Golubovski (Golubovsky and Sokolova, 1973;Golubovsky, 1978) found that 1-2% of second chromosomes in nature carried a heterozygous 1(2)lgl mutation. Cloning and molecular analysis of the locus (Mechler et al, 1985) revealed that the vast majority of 1(2)lgl mutations are associated with terminal chromosome deficiencies resulting in 3' truncations of the gene, which is transcribed from proximal to distal.…”
Section: A Novel Drosophila Telomere Elongation Mechanismmentioning
confidence: 99%
“…The 1(2)gl gene is the most distal locus on the left arm of chromosome 2. Golubovski (Golubovsky and Sokolova, 1973;Golubovsky, 1978) found that 1-2% of second chromosomes in nature carried a heterozygous 1(2)lgl mutation. Cloning and molecular analysis of the locus (Mechler et al, 1985) revealed that the vast majority of 1(2)lgl mutations are associated with terminal chromosome deficiencies resulting in 3' truncations of the gene, which is transcribed from proximal to distal.…”
Section: A Novel Drosophila Telomere Elongation Mechanismmentioning
confidence: 99%